ISU-ISU DINAR DAN DIRHAM - Fatma Khalieda (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Lately there dinars are very active in Malaysia. They argue that if this return is achieved, all modern economic diseases such as inflation, credit, and unemployment will be resolved. M. Syafii Antonio says the current banknote system opens the door to fraudulent acts carried by financial institutions on Wall Street. That we should go back to the golden system where the currency is made of gold and tighten the monitoring system and urge Muslim countries to return to the